2020
DOI: 10.5455/medarh.2020.74.279-284
|View full text |Cite
|
Sign up to set email alerts
|

"Second-look" Micro Testicular Sperm Extraction (MicroTESE) in Patients with Non-obstructive Azoospermia Following Histopathological Analysis

Abstract: Introduction: Microdissection testicular sperm extraction (microTESE) is considered the gold standard method for surgical sperm retrieval among patients with non-obstructive azoospermia (NOA). Aim: This study aimed to evaluate the correlation between histopathological findings after failed microTESE procedure and outcomes of the „second-look“ procedure and to provide insight into the most common histopathological patterns after testicular biopsy within our population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…The increased stiffness of KS testes is due to seminiferous tubule hyalinization. However, in our study, we observed obvious seminiferous tubule hyalinization in the testes of 10 participants without KS who had a JS of 1–2, which is consistent with previous research ( 29 ). Seminiferous tubule hyalinization has been reported not only in the testes of those with KS, but also in the undescended testes and testes of patients with severe oligozoospermia or NOA ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…The increased stiffness of KS testes is due to seminiferous tubule hyalinization. However, in our study, we observed obvious seminiferous tubule hyalinization in the testes of 10 participants without KS who had a JS of 1–2, which is consistent with previous research ( 29 ). Seminiferous tubule hyalinization has been reported not only in the testes of those with KS, but also in the undescended testes and testes of patients with severe oligozoospermia or NOA ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the most common histological pattern was Sertoli cell only syndrome (58.4%) followed by a mixed pattern (22.8%) while the least represented pattern was GCMA (4.6%). This is in accordance with the study of Spahovic et al [7] and Mushtaq [15]. SCOS is one of the most common, but also the most serious type of nonobstructive azoospermia and can have various etiology, including gonadotropin deficiency, cryptorchidism, orchitis, prostate cancer hormonal therapy, radiation, Klinefelter syndrome [4].…”
Section: Discussionsupporting
confidence: 91%
“…The most common morphological patterns identified in the testicular biopsies of NOA patients following negative sperm retrieval during a micro-TESE procedure are: hypospermatogenesis (HS), germ cell maturation arrest (GCMA), Sertoli-cell only syndrome (SCOS), seminiferous tubule hyalinization (STH) and mixed pattern (MP). Therefore, histopathological analysis is also critical for the proper selection of patients for the "second look" micro-TESE attempt, which increases the possibility for successful infertility treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…Available data favor the use of micro-TESE as it has fewer operative complications, in addition to a higher success rate of sperm retrieval approaching 50% of the cases. This percentage could even be increased by achieving an optimal pre-operative testosterone serum level of 250 ng dl−1 [19][20][21][22]. Multiple centers started to offer peri-pubertal sperm retrieval through the technique mentioned above with cryopreservation of sperm, under the premise of a higher success rate due to normal hormonal profile and a lesser degree of fibrosis in such an age.…”
Section: Infertilitymentioning
confidence: 99%